Russian foreign policy towards the Nagorno-Karabakh conflict : Prudent geopolitics, incapacity or identity? - Abushov, Kavus (Routledge, 2019)
This article fundamentally re-examines Russia’s foreign policy towards the Nagorno-Karabakh conflict, trying to explain the sources of its behavior. In particular, it assesses its foreign policy in the light of its strategic interests, material capabilities versus incapacity and identity. A central question is why Russia does not give enough support to a settlement based upon modus vivendi. It argues that whereas Russia does not have the capacity to achieve a final solution to the conflict, it has ample resources to obtain a solution that would release the occupied regions outside Nagorno-Karabakh and leave the status of the territory unresolved for an indefinite future. The article sheds light on the factors undergirding its policy towards the Nagorno-Karabakh conflict, arguing for the utility of a different perspective on its commitments. It adds new insights to the existing body of literature on Russia’s policies towards Nagorno-Karabakh conflict such as incapacity and identity with implications for a better understanding of broader Russian foreign policy. Moreover, with South Ossetia and Crimea in the spotlight, Russian foreign policy towards the conflict has been viewed through geopolitics and neo-imperialism, but remains little understood.
East European Politics
Keywords: Europe, Eastern -- Politics and government -- Periodicals.; Nagorno-Karabakh Conflict, 1988-1994.; Azerbaijan -- Relations -- Russia (Federation).